Bone marrow transplantation: ethical aspects - Fasanella, Giuseppe; Sgreccia, Elio (Medicina e Morale, 1988)
Transplantation of an organ or tissue nowadays represents a real prospect of cure for several patients. Scientific advances, especially in the biological and genetic fields, have made it possible to better address the crucial problem of rejection. However, the story of transplantation still remains an intricate, painful, confusing one.